CLINICAL AND PATHOPHYSIOLOGICAL ASPECTS OF VIRAL HEPATITI (International journal of artificial intelligence, 2026)
Viral hepatitis represents a major global health burden, affecting millions of people worldwide and causing significant morbidity and mortality. The disease is primarily caused by hepatotropic viruses (hepatitis A, B, C, D, and E), each with distinct transmission routes, clinical manifestations, and long-term outcomes. Chronic viral hepatitis, particularly types B and C, is strongly associated with cirrhosis and hepatocellular carcinoma, making it a critical focus for prevention and treatment. This article reviews the pathophysiological mechanisms, clinical features, and pharmacological management of viral hepatitis, highlighting current challenges and advances in antiviral therapy.